The influence of high energy irradiation on electrical and dissipative properties of silicon single crystals - Pelikhaty, N.M.; Rokhmanov, N.Ya.; Onischnko, V.V. (Functional Materials, 2006)
Behavior of internal friction δ and electric resistance in silicon single crystals with low dislocation density (10-100 cm⁻²) has been studied during of bombardment with α-particles. Effect of strengthening has been found as well as change of direct hysteresis into reverse one in amplitude dependence of internal friction at increasing α-irradiation dose rate. The fact is explained by blocking of charged dislocations by radiation-induced vacancies and areas of charge separetion formed due to secondary infrared irration.